2017
DOI: 10.4037/ccn2017178
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Acute Kidney Injury Due to Contrast Material: How Nurses Can Improve Patient Safety

Abstract: BACKGROUND Acute kidney injury due to contrast material occurs in 3% to 15% of the 2 million cardiac catheterizations done in the United States each year. OBJECTIVE To reduce acute kidney injury due to contrast material after cardiovascular interventional procedures. METHODS Nurse leaders in the Northern New England Cardiovascular Disease Study Group, a 10-ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 56 publications
0
4
0
1
Order By: Relevance
“…A study by Lambert et al (2017) titled "reducing contrast-induced acute kidney injury: how nurses can improve patient safety?" during 2007 to 2012 to improve quality and reduce the incidence of contrast-induced nephropathy on 20147 patient candidates for angioplasty in 10 centers in the north of England indicated that the standardization of the best evidence-based practices in nursing care could reduce the incidence of contrast-induced acute kidney injury (38).…”
Section: Discussionmentioning
confidence: 99%
“…A study by Lambert et al (2017) titled "reducing contrast-induced acute kidney injury: how nurses can improve patient safety?" during 2007 to 2012 to improve quality and reduce the incidence of contrast-induced nephropathy on 20147 patient candidates for angioplasty in 10 centers in the north of England indicated that the standardization of the best evidence-based practices in nursing care could reduce the incidence of contrast-induced acute kidney injury (38).…”
Section: Discussionmentioning
confidence: 99%
“…15,17,24 In this sense, the role of the nurse is highlighted, in which the authors seem unanimous in affirming their importance, mainly in the recognition of possible complications. 16,20,24,19 In addition, nurses need to be updated on the guidelines for the treatment of this clientele and must be able to identify the associated risk factors, such as the use of anticoagulants and antiplatelet agents associated with the risk of bleeding after the procedure. 18,20 In the context of basic human needs, the elimination of body waste as a concern was addressed in addressing the prevention of CIN in an experimental study.…”
Section:  Nursing Care For the Prevention And Correction Of Post-cta Complicationsmentioning
confidence: 99%
“…Iopromide, a new nonionic hypotonic contrast agent commonly used in PCI, has a direct toxic effect on renal tubular epithelial cells, such as the vacuolation of proximal tubules, interstitial edema, and renal tubular degeneration (Tan et al, 2017). The cytotoxic mechanisms induced by contrast agents include apoptosis, cell inflammation, and calcium homeostasis damage (Rear et al, 2016;Lambert et al, 2017). The flow resistance in the renal tubules increases after renal tubular epithelial cells are injured, and the renal interstitial pressure can reach up to 50 mmHg.…”
Section: Introductionmentioning
confidence: 99%